Real-World Dual Antiplatelet Therapy Following Polymer-Free Sirolimus-Eluting Stent Implantations to Treat Coronary Artery Disease - Krackhardt, Florian; Waliszewski, Matthias; Kočka, Viktor; Toušek, Petr; Janek, Bronislav; Hudec, Martin; Lozano, Fernando; Roman, Koldobika Garcia-San; Del Blanco, Bruno Garcia; Mauri, Josepa; Heang, Tay Mok; Ahn, Tae Hoon; et al. (Cardiovascular drugs and therapy, 2020)
OBJECTIVES: The objective of this post hoc analysis was to analyze real-world dual antiplatelet therapy (DAPT) regimens following polymer-free sirolimus-eluting stent (PF-SES) implantations in an unselected patient population. METHODS: Patient-level data from two all-comers observational studies (ClinicalTrials.gov Identifiers: NCT02629575 and NCT02905214) were pooled and analyzed in terms of their primary endpoint. During the data verification process, we observed substantial deviations from DAPT guideline recommendations. To illuminate this gap between clinical practice and guideline recommendations, we conducted a post hoc analysis of DAPT regimens and clinical event rates for which we defined the net adverse event rate (NACE) consisting of target lesion revascularization (TLR, primary endpoint of all-comers observational studies) all-cause death, myocardial infarction (MI), stent thrombosis (ST), and bleeding events. A logistic regression was utilized to determine predictors why ticagrelor was used in stable coronary artery disease (CAD) patients instead of the guideline-recommended clopidogrel. RESULTS: For stable CAD, the composite endpoint of clinical, bleeding, and stent thrombosis, i.e., NACE, between the clopidogrel and ticagrelor treatment groups was not different (5.4% vs. 5.1%, p = 0.745). Likewise, in the acute coronary syndrome (ACS) cohort, the NACE rates were not different between both DAPT strategies (9.2% vs. 9.3%, p = 0.927). There were also no differences in the accumulated rates for TLR, myocardial infarction ([MI], mortality, bleeding events, and stent thrombosis in elective and ACS patients. The main predictors for ticagrelor use in stable CAD patients were age < 65 years, smaller vessels, treatment of ostial and calcified lesions, and in-stent restenosis. CONCLUSION: Within the framework of a post hoc analysis based on a real-world, large cohort study, there were no differences in the combined endpoint of major adverse cardiac events (MACE), bleeding and thrombotic events for clopidogrel and ticagrelor in stable CAD or ACS patients. Despite the recommendation for clopidogrel by the European Society of Cardiology (ESC), real-world ticagrelor use was observed in subgroups of stable CAD patients that ought to be explored in future trials.
Keywords: Coronary Artery Disease; nemoci koronárních tepen; Hemorrhage; Coronary Thrombosis; Dual Anti-Platelet Therapy; Observational Studies as Topic; pozorovací studie jako téma; Humans; Drug-Eluting Stents; lidé středního věku; koronární angioplastika; multicentrické studie jako téma; Guideline Adherence; Female; rizikové faktory; Aged; Sirolimus; duální protidestičková léčba; inhibitory agregace trombocytů; výsledek terapie; sirolimus; senioři; lidé; Ticagrelor; Prosthesis Design; časové faktory; Dual antiplatelet therapy; kardiovaskulární látky; Practice Guidelines as Topic; ženské pohlaví; dodržování směrnic; Male; Sirolimus-eluting stent; Middle Aged; stenty uvolňující léky; koronární trombóza; Treatment Outcome; Polymer-free; směrnice pro lékařskou praxi jako téma; Aged, 80 and over; Practice Patterns, Physicians'; lékařská praxe - způsoby provádění; Percutaneous Coronary Intervention; senioři nad 80 let; krvácení; Cardiovascular Agents; Clopidogrel; Risk Assessment; protézy - design; mužské pohlaví; Platelet Aggregation Inhibitors; Time Factors; hodnocení rizik; Multicenter Studies as Topic; Risk Factors